2015
DOI: 10.1177/1526602815601405
|View full text |Cite
|
Sign up to set email alerts
|

Late Rupture of Abdominal Aortic Aneurysm After Previous Endovascular Repair

Abstract: Graft-related endoleaks appear to be the predominant causes of late aneurysm rupture. Quality of and compliance with post-EVAR surveillance are important factors in late rupture; a large proportion of late ruptures are amenable to endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 51 publications
7
116
1
3
Order By: Relevance
“…Recent studies have shown that the incidence of delayed rupture is 0.9% and that it occurs mainly because of type I endoleak [1]. For EVAR-suitable patients with rupture due to type I or III endoleaks, endovascular procedures are considered a superior treatment option compared with surgical conversion [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the incidence of delayed rupture is 0.9% and that it occurs mainly because of type I endoleak [1]. For EVAR-suitable patients with rupture due to type I or III endoleaks, endovascular procedures are considered a superior treatment option compared with surgical conversion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed rupture after endovascular aortic aneurysm repair (EVAR) is a potentially fatal complication that mainly occurs because of type I endoleak [1]. Delayed rupture caused by an isolated type II endoleak is rare [2], and its management has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, type III endoleak is the second commonest cause of post-EVAR aneurysm rupture. 27 These studies do not necessarily differentiate between type IIIa and IIIb endoleaks; however, fabric degradation with type IIIb endoleak is becoming more recognized as a late failure modality. 28 Treatment of type IIIb endoleak can be endovascular or open.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality data favored an endovascular approach for repair of rupture after EVAR. Also, the importance of post-EVAR follow-up must be stressed, as 37 % of ruptures occurred in patients who were non-compliant with surveillance [70]. Follow-up is typically performed with CTA, which has inherent risks due to contrast and radiation exposure.…”
Section: Follow-up Imagingmentioning
confidence: 99%